An experimental investigation of the pressure distributions on five bodies of revolution at Mach numbers of 2.45 and 3.19 - Marson, G. B.; Socha, W.; Keates, R. E. (College of Aeronautics, Cranfield, 1954)
Measurements have been made in the College of Aeronautics 2½ x2½ intermittent high speed tunnel of the pressure distribution on five non lifting bodies of revolution of different nose angles at zero incidences. The tests were made at Mach numbers of 2.45 and 3.19. The results are compared with the pressure distributions given by two approximate theoretical methods, and good agreement is found at the Mach numbers used.